Effect of Pregabalin on Perioperative Headache in Patients with Aneurysmal Subarachnoid Hemorrhage: A Randomized Double-Blind, Placebo-Controlled Trial - Lionel, Karen Ruby (J Neurosci Rural Pract, 2019)
Background Patients with acute aneurysmal subarachnoid hemorrhage (aSAH) experience excruciating headache that is difficult to manage in resource-constrained settings. Pregabalin’s (β-isobutyl-GABA) analgesic, antiepileptic, and antiemetic properties make it an attractive adjuvant in pain management for these patients. Methods We conducted a double-blind, placebo-controlled, randomized clinical trial on 40 aSAH patients undergoing aneurysmal clipping to assess the effect of perioperative pregabalin in decreasing perioperative headache, anesthetic, and opioid requirement. Patients received either pregabalin (75 mg) or placebo twice daily soon after admission till 24-hour postoperative, in addition to paracetamol 650 mg thrice daily. Headache assessed using a visual analog scale (VAS) at five time points was compared using a mixed effects regression model. Results Pain assessed by VAS declined significantly more from the baseline in pregabalin recipients compared with placebo at preinduction (–3.6 vs.–1.8; p = 0.004), 12-hour (4.3 vs. 2.8; p = 0.014), and 24-hour postsurgery (4.7 vs. 2.9; p = 0.007), but not at the 6-hour postoperation (4.9 vs. 3.8; p = 0.065). Pregabalin recipients required a lower minimum alveolar concentration of sevoflurane to maintain a prespecified bispectral index of 40 and 60 (0.8 vs. 0.9; p = 0.014) and required fewer rescue analgesic doses in the 24  hours following surgery (1.8 vs. 3.3; p = 0.005). The intraoperative fentanyl requirement was not significantly different between the groups (10 μg/kg vs. 11.4 μg/kg; p = 0.065). There was no significant difference in the sedation scores. Conclusions Pregabalin 75 mg administered twice daily, during the perioperative period, was an effective adjunct in the management of the severe headache experienced by patients with aSAH and decreased the opioid and anesthetic requirement without significantly increasing sedation.